3(-1a-6)=-18

Simple and best practice solution for 3(-1a-6)=-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-1a-6)=-18 equation:


a in (-oo:+oo)

3*(-1*a-6) = -18 // + 18

3*(-1*a-6)+18 = 0

3*(-a-6)+18 = 0

3*(-a-6)+18 = 0

-3*a = 0

-3*a = 0

-3*a = 0 // : -3

a = 0

a = 0

See similar equations:

| 3(-3+d)=21 | | 2l+2w=50 | | 6(-6x+10)=348 | | 2(-3k-2)=-58 | | 4(-2+2x)=64 | | 5(3+3a)=45 | | 4(6-3d)=-108 | | 5(7d-5)=80 | | 3(-3-d)=24 | | 6n+3=-3n+30 | | -k+6=42+3k | | 4w+9=2w+29 | | 9+4d=3d+12 | | 6+7a=3a-22 | | 6w+9=33+3w | | x^2+3x+4=8 | | 44/7+88=b | | -2-5x=x-44 | | 9+7x=x+15 | | d+7=40+4d | | 3d-9=0+6d | | 5a+6=-54-7a | | 3m-9=m-1 | | 3d-8=-5+6d | | 3y^2-13y+4= | | -10(-9x)= | | x^2+8x-11=9x-5 | | 62/7*20=y | | -10(9x)= | | 6m-5=4m+17 | | -m-10=-3+6m | | w-5=6w-50 |

Equations solver categories